2014
DOI: 10.1515/bjdm-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-releasing dental restorative materials: An update

Abstract: SUMMARYThe fluoride ion has a well-established beneficial role in dentistry in protecting the teeth from assault by caries. It is known to contribute to the dynamic mineralisation process of the natural tooth mineral, and also to become incorporated with the mineral phase, forming a thin layer of fluorapatite. This is more resistant to acid attack than the native hydroxyapatite, hence protects the tooth against further decay. Other recently discovered aspects of the role and uptake of fluoride will also be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 81 publications
0
11
0
8
Order By: Relevance
“…All GICs in the current study continued to release fluoride even at the end of measurement. It was reported that the fluoride release from GICs was detected for up to 5 years 31,32) . The continuation of fluoride diffusion may result from slow acid-base reaction in the bulk of the materials.…”
Section: Fluoride Releasementioning
confidence: 99%
“…All GICs in the current study continued to release fluoride even at the end of measurement. It was reported that the fluoride release from GICs was detected for up to 5 years 31,32) . The continuation of fluoride diffusion may result from slow acid-base reaction in the bulk of the materials.…”
Section: Fluoride Releasementioning
confidence: 99%
“…Nhờ có những ưu điểm như khả năng giải phóng fluoride, hiệu quả trong việc bảo vệ và ngăn ngừa sâu răng tái phát, tính thẩm mĩ (khá giống răng tự nhiên về màu sắc và độ trong mờ) [3]- [5], xi măng GIC xuất hiện và phát triển như một bước tiến trong lĩnh vực vật liệu y sinh nói chung và lĩnh vực nha khoa nói riêng. Bên cạnh đó, GIC còn được dùng như một loại xi măng dán tăng lực dính cho mão, cầu của răng, vật liệu trám cho cả răng sữa, răng vĩnh viễn ở mọi lứa tuổi, tái tạo cùi răng cho phục hình, chất bảo vệ tủy và trám lót [3], [4].…”
Section: Giới Thiệuunclassified
“…Mineralizasyon, çekirdek görevi gören kalsiyum florapatit nano kristalleri varlığından ve kısmen mineralizasyona yardımcı iyonların kaynağı olan hidroksiapatit varlığından kaynaklanmaktadır. 36 Cam karbomer geleneksel CİS'lere kıyasla çok ince partikül boyutuna sahiptir. Bu durum cam yapının kolay bir şekilde çözünerek florapatite dönüşebildiğini düşündürmektedir.…”
Section: Cam Karbomerunclassified
“…38 Üretici firma cam karbomer simanın biyomimetik (doğal, taklit yeteneği olan) bir materyal olduğunu bildirmiştir. 22,36 Cam karbomer, ek bir karbon zincirine sahiptir ve nano boyutlu toz parçacıkları ve ikincil doldurucu olarak fluorapatit içermekle beraber serbest monomer içermez. Mine ya da dentine herhangi bir işlem uygulamadan bağlanabilirler.…”
Section: Cam Karbomerunclassified
See 1 more Smart Citation